Answer: C
Step-by-step explanation: 3x and 5x both have x
Y = 1 + i
<span>(1 + i)^3 - 3 * (1 + i)^2 + k - 1 = -i </span>
<span>(1 + 3i + 3i^2 + i^3) - 3 * (1 + 2i + i^2) + k - 1 = -i </span>
<span>1 + 3i - 3 - i - 3 - 6i + 3 + k - 1 = -i </span>
<span>1 - 3 - 3 + 3 - 1 + 3i - i - 6i + k = -i </span>
<span>-3 - 4i + k = -i </span>
<span>k = 4i - i + 3 </span>
<span>k = 3i + 3 </span>
<span>k = 3 * (1 + i) </span>
<span>k = 3y</span>
from both sides of the equation.
Answer:
Apply the distributive property.
6 ⋅ 5 + 6 (-3x) = -4 x - 12
Multiply
6 by 5 . 30 + 6 (-3 x) = - 4 x - 12
Multiply
− 3 by 6 . 30 - 18 x = - 4 x - 12
Add
4 x to both sides of the equation.
30 - 18 x + 4 x = - 12
Add
− 18 x and 4 x . 30 - 14 x = - 12
Subtract
30
from both sides of the equation.
- 14 x = - 12 - 30
Subtract
30 from
− 12 . - 14 x = - 42
x = 3
Step-by-step explanation:
Answer:
-2
Step-by-step explanation:
The average rate of change on an interval is ...
average rate of change = (amount of change)/(width of interval)
= (-3 -1)/(1 -(-1)) = -4/2 = -2
The average rate of change between (-1, 1) and (1, -3) is -2.
Answer:
x=15
Step-by-step explanation:
Substitute the values to check your answer...
(x²-11x)=60
(15²-11*15) =60.